Antiangiogenic agents targeting different angiogenic pathways have opposite effects on tumor hypoxia in R-18 human melanoma xenografts - Gaustad, Jon-Vidar (BMC Cancer, 2017)
BACKGROUND: Studies comparing the effect of antiangiogenic agents targeting different angiogenic pathways are sparse. The purpose of this study was to compare the effect of properdistatin and sunitinib treatment in a preclinical model of malignant melanoma. Properdistatin is a small peptide derived from the thrombospondin-1 domain of the plasma protein properdin, and sunitinib is a tyrosine kinase inhibitor targeting several receptors including the vascular endothelial growth factor receptors. METHODS: R-18 human melanoma xenografts growing in dorsal window chambers were treated with properdistatin, sunitinib, or vehicle. Parameters describing the morphology of tumor vasculature were assessed from high-resolution transillumination images, and BST (blood supply time; the time needed for arterial blood to flow from the main supplying artery to downstream microvessels) was assessed from first-pass imaging movies recorded after a bolus of fluorescence-labeled dextran had been administered intravenously. Tumor hypoxia was assessed from immunohistochemical preparations of the imaged tissue by using pimonidazole as a hypoxia marker. RESULTS: Properdistatin treatment selectively removed small-diameter vessels and reduced BST, whereas sunitinib treatment reduced the density of small- and large-diameter vessel similarly and did not change BST. These observations imply that properdistatin treatment reduced geometric resistance to blood flow and improved vascular function, whereas sunitinib treatment did not affect vascular function. Accordingly, sunitinib-treated tumors showed higher hypoxic fractions than properdistatin-treated tumors. CONCLUSIONS: Properdistatin and sunitinib both inhibited angiogenesis, but had distinctly different effects on vascular morphology, vascular function, and extent of hypoxia in R-18 human melanoma xenografts. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-017-3404-4) contains supplementary material, which is available to authorized users.